Deng dai Xianggang : yong yuan de Xianggang ren = Waiting for Hong Kong - Lam, Edward (Hangzhou : Zhejiang da xue chu ban she, 2009)
Summary in vernacular field only.
Keywords: Popular culture -- China -- Hong Kong; Hong Kong (China) -- Social life and customs